Analysis of the effect of allylpyrocatechol (Piper betle Linn.) on oxidative stress resistance enzymes in Staphylococcus aureus and nadph oxidase in polymorphonuclear leukocytes / Noor Faradilla Abdullah - Abdullah, Noor Faradilla (2020)
Allylpyrocatechol (APC) is a major phenolic constituent in Piper betle L. leaves extract which consists of benzene ring with hydroxyl groups. It displays antimicrobial activity against Staphylococcus aureus (S. aureus), however, study about its effects on the stress response mechanism of this organism is limited. An optimised method was developed for APC isolation based on elution from analytical RP-HPLC in isocratic mode using ratio 45% acetonitrile: 55% aqueous phosphoric, where APC was proven to be the major constituent with yield of 78% and purity of 97%. In this study, expression of katA, sodA, sodM, and ahpC genes of S. aureus in response to APC (2 mg/mL) was analyzed by RT-qPCR in reference to gyrA and 16S rRNA. Corresponding activities of the superoxide dismutases (SOD), alkylhydroperoxide reductase C (ahpC) and catalase were also investigated. APC increased expression of sodA (2.478), sodM (1.667) and ahpC (6.53), but not katA (0.706) gene in comparison to untreated S. aureus cells. Corresponding increased of total SOD (12.24 U/ml) and AhpC (A310 nm=0.672) activities but decreased catalase activity (1.8 x 104 U/l) were observed in APC-treated cells. APC reduced the generation of superoxide anion through the inhibition of NADPH oxidase. APC-treated PMNs had lower relative light unit (RLU) of 0.003 within 30 minutes (P<0.05) compared to PMNs with S. aureus (0.319) suggesting reduction in oxidative bursts. The NBT assay resulted on 0.330 of absorbance reading at 560 nm, which indicated lower extracellular superoxide level released by neutrophils with APC treatment. Similarly, expression of CYBB (gp91- phox) and NCF2 (p67-phox) in APC-treated PMNs challenged with S. aureus were down regulated at 0.473-fold and 0.39-fold respectively. In addition, APC was able to inhibit S. aureus more effectively than 10 mM H2O2 with only 8.9% cells survived than H2O2 10 mM H2O2 (87%). Similarly, APC-treated cells showed significant difference (p<0.05) in the percentage of survival (10%) in comparison to diamide (10 mM) killing (15%) after 1 hour treatment. The treatment of paraquat (10 mM) with APC reduced the number of cells survived to 7%. APC more effectively reduced the number of viable S. aureus cells compared to hydrogen peroxide (10 mM), diamide (10 mM) and paraquat (10 mM). This study has provided insight on regulatory of stress responses, but the relevance of these genes in survival, repair of damage, or cellular recovery have not yet been revealed.